EFEKTIVITAS MASA WAKTU PENANGKAPAN TINDAK PIDANA PSIKOTROPIKA PERSPEKTIF UNDANG-UNDANG PSIKOTROPIKA DAN UNDANG-UNDANG NARKOTIKA PADA SATRESNARKOBA POLRES SLEMAN - MEDDIF WISUDAWAN BIMA SAKTI KUSNAN KUSNAN (Advances in Police Science Research Journal, 2019)
Drugs have now become a serious problem that is currently faced by our nation, be it narcotics or psychotropic groups. It has been the duty of the police in cracking down firmly on suspected perpetrators of psychotropic crimes, as stipulated in Article 13 of Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia. However, in the crackdown, there was an error in procedure, which at the stage of fulfillment of 2 (two) evidence tools for the condition of determining the status of the suspect and the arrest of him. This is due to the unregulated time of arrest in Law No. 5 of 1997 on Psychotropics, so the length of time of arrest for this crime is 1x24 hours, while the time required to wait for the results of lab tests of evidence is at least 3x24 hours.The preparation of this thesis uses a qualitative approach with the type of field research. Then to discuss the problem of the ineffectiveness of the prosecution of this psychotropic crime, the researcher uses the theory of effectiveness and concepts related to the focus of the problem in this thesis. The results of this study can be concluded that the implementation of psychotropic crime action based on Law No. 5 of 1997 on Psychotropics is no longer relevant. Because the timeframe for the arrest was not regulated, this criminal act only had a period of time for arrest of 1x24 hours (Art. 19 KUHAP). It is different from Law Number 35 of 2009 concerning Narcotics, because it provides for a 3x24 hour arrest period and can be extended for 3x24 hours. This resulted in the ineffective prosecution of psychotropic crimes by the Sleman Police Narcotics Unit, which could lead to legal problems (pretrial) in the future for the Indonesian National Police. Keywords: Effectiveness, Time of Arrest, Psychotropic Law, Narcotics Law